The Relationship between Entrepreneurial Orientations and Occupational Performance at TUMS Student Health Center - Asadollah Khahande Karnama; Amer Dehghan Najm Abadi; Mehdi Tajpour (Tehran University of Medical Sciences, 2017)
Background and Aim: The study of relationship between entrepreneurial orientation and performance leads to the improved competitive performance of organizations. The purpose of the present study is to determine the relationship between entrepreneurial orientation and occupational performance. Materials and Methods: This study is a descriptive-analytical applied research. As regards the type of collected data, the present study is quantitative with the standard questionnaire of Lumpkin and Dess for the measurement of entrepreneurial orientation and the standard questionnaire of Byrne and Conway for the measurement of occupational performance. One hundred and eight employees at Tehran University of Medical Sciences (TUMS) Student Health Center formed the sample of the study. Data analysis was done by using SPSS and SMART PLS in two parts: part of measurement model and structural part. Results: The results indicate a positive and meaningful relationship between entrepreneurial orientation and its dimensions (innovation, risk-taking, and proactivity) and the staff members' occupational performance. Also, the dimensions of entrepreneurial orientation have a high correlation with each other, but they do not have the same effect on occupational performance. Regarding the importance of each entrepreneurial orientation dimension, it is proposed that facility managers define activities that lead to the increase of occupational performance.  Conclusion: Considering the results of this study, taking measures to enhance the staff's entrepreneurial activities in health centers can lead to the increase of job performance in these centers.